Lacustrine Sediments Bacterial Community Structure Vertical Succession of the Linxia Basin, NE Tibetan Plateau: Significance for Paleoenvironment Reconstruction - Xu, Song; Wang, Jingjing; Zhang, Xiaoxia; Yang, Rong; Zhao, Wei; Huang, Zhiyong; Wang, Yongli (Frontiers in Earth Science, 2022)
The study on sediments in the marginal basins of the Tibetan Plateau is of great significance for global climate change. The geological information of the Linxia Basin has been intensely investigated; however, the profiles of the microbial communities in this basin remain largely unknown. Here, based on the 16S rRNA high-throughput sequencing method, the bacterial community structure vertical succession is studied with different thicknesses of sedimentary samples. The bacterial community with a total of 1,729,658 paired reads distributed within 1,042 phylogenetic amplicon sequence variants (ASVs) from twenty sediments, and three surrounding soil samples were sequenced. First, high-throughput sequencing results highlight the surrounding soil sample bacterial community structures were significantly different from those recovered from the sediment samples. In addition, as observed in the PCoA and PERMANOVA, there is a dramatic change shift event of the community structure at M311. Our data suggest that shifts in relative abundances of the abundant taxa (˃1%) and the significant variations in the diversity of bacterial community implied community structure responses to changes in different sedimentary layers. Predicted community function changes demonstrate that the sediment bacterial community aerobic chemoheterotrophy has been significantly increased, and we believe that the possible influence of the lithofacies changes from the anaerobic system to the aerobic environment, possibly accompanied by the significant uplift of the plateau that has previously been associated with enhanced aridity in Central Asia at ∼8 Ma. Taken together, these results illustrate the potential for the microbial community as a biological indicator in sediment ecosystems to reconstruct paleoenvironments.